Using uncertainty as a learning opportunity during pre-lesson conferences in the teaching practicum. (November 2019) - Costache, Oana; Becker, Eva; Staub, Fritz; Mainhard, Tim
Abstract: This qualitative study examined transcripts and video-data from 32 pre-lesson conferences of 14 cooperating teacher-student teacher dyads during the teaching practicum. It used a linguistic approach to capture student teacher uncertainty, while also considering their teaching experience and pedagogical content knowledge. Cooperating teachers' responses to uncertainty were explored in relation to student teachers' instructional quality (as perceived by the student teachers and their pupils). This study illustrates the potential of using uncertainty as a learning opportunity and suggests new possibilities for how cooperating teachers could constructively respond to uncertainty in mentoring conversations. Highlights: Student teachers' uncertainties in lesson planning can be identified with linguistic cues. Pre-lesson conferences can prepare student teachers for the uncertainty of actual practice. Student teachers' uncertainty mainly pertained to instructional design and content. Student teachers with higher pedagogical content knowledge discussed their uncertainties more openly. Cooperating teachers can take on different roles to support inquiry and knowledge development.